Conclusive evidence of endotoxaemia in biliary obstruction. Issue 2 (1st February 1998) - Clements, W D B; Erwin, P; McCaigue, M D; Halliday, I; Barclay, G R; Rowlands, B J
Abstract : Background —Endotoxaemia is implicated in the pathophysiology of obstructive jaundice. The EndoCab enzyme linked immunosorbent assay (ELISA) is a novel assay which measures endogenous antibody (IgG) to the inner core region of circulating endotoxins (ACGA). Aims —To investigate the significance of endotoxaemia in biliary obstruction using the EndoCab assay and assess the specificity of the humoral response to endotoxin compared with an exogenous antigenic challenge (tetanus toxoid, TT). Methods —Three groups of adult male Wistar rats were studied: no operation, sham operation, and bile duct ligation for 21 days (BDL). In the second study, rats rats received prior immunisation with TT. Results —In the preliminary experiment, plasma ACGA was significantly increased in the BDL group (306.6 (18.3)% versus 119.9 (6.7)% and 105.2 (4.6)% in the sham and no operation groups, respectively; p<0.001). Although the mean endotoxin concentration in the BDL group was greater than that in the control groups this was not significant. There was a strong positive correlation between ACGA and endotoxin concentrations (p=0.0021). In the second study mean ACGA after 21 days of BDL was significantly elevated (267.1 (31.2)% versus 101.6 (21.2)% at baseline, p<0.0001). ACGA was unaffected in the other two groups. TT antibody concentrations fell in all three groups; only in the BDL group was the fall significant (97.6 (5.3)% versus 78.8 (4.2)% at baseline, p<0.05). Conclusions —The specific rise in ACGA supports the hypothesis that endotoxin has an integral role in the pathophysiology of obstructive jaundice. The production of anticore glycolipid antibodies specifically reflects systemic endotoxaemia in this model. The EndoCab assay provides a novel, sensitive, and specific method for endotoxin detection.